Protective effect of sakuranetin in brain cells of dementia model rats - Li, Chen; Hu, Chunting; Wang, Ruili; Wang, Hui; Ma, Qiaoya; Chen, Songsheng; He, Ya (Cellular and Molecular Biology, 2019)
Alzheimer's disease (AD) is a high-incidence neurodegenerative disease with complex and diverse pathogenesis. With aging of the population and continuous improvement of living standards, the incidence of AD is on the increase. Therefore, there is need to develop more effective AD drugs in order to improve the quality of life of the elderly. Sakuranetin (SAK) is a dihydroflavonoid compound extracted from plants. It has many physiological properties. In this study, the effect of SAK on spatial discrimination in a rat model of cognitive dysfunction exposed to D-galactose was investigated with respect to its effect on malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GPx) levels, and on the expressions of interleukin-6 (IL-6), tumor necrosis factor-Î± (TNF-Î±) and nuclear factor-ÎºB inhibitory factor-Î± (IÎºBÎ±) in hippocampus of rats. The results obtained suggest that SAK may exert protective effects on brain cells through anti-oxidation mechanism. Moreover, the improvement in learning and memory impairment by SAK may also be related to the inhibition of inflammatory mediators in brain tissue. These findings provide scientific evidence that can be exploited for more effective treatment of Alzheimer's disease.